1944
DOI: 10.1017/s0021859600019742
|View full text |Cite
|
Sign up to set email alerts
|

The Placement of fertilizers: II. Cereals

Abstract: Results are reported of sixteen replicated experiments on spring-sown barley and oats in south-east England to compare fertilizer sown in the drills with fertilizer broadcast. In thirteen of the experiments, fertilizer in the drills gave significantly greater yields of grain and straw than fertilizer broadcast, in two of the experiments the differences between the two were not significant; in only one experiment was the grain yield significantly greater where the fertilizer was broadcast.Fertilizers were twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1945
1945
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…Results of these experiments indicate that banded K is more efficient than broadcast K for corn. Thus, they are in agreement with most of the results reported earlier by others (5,9,11,12,20).…”
Section: Discussionsupporting
confidence: 93%
“…Results of these experiments indicate that banded K is more efficient than broadcast K for corn. Thus, they are in agreement with most of the results reported earlier by others (5,9,11,12,20).…”
Section: Discussionsupporting
confidence: 93%
“…Stanford and Pierre (1953) in a review article state: "Various references are found to the effect that when drilled, only about half as much phosphorus fertilizer may be required to produce a given yield increase as when the fertilizer is broadcast." They cited Smith (1947), Lewis andStrickland (1944), Norum andYoung (1950), and Reith (1952), as references who support the concept of doubling the row applied rate for broadcast purposes. A thorough check on each of the cited investigations revealed that in some cases the authors had not concluded anything about the relative rates of row and broadcast.…”
Section: G a Peterson D H Sander P H Grabouski And M L Hooker2mentioning
confidence: 99%
“…However, his expenment was not designed to test the 2: I broadcast to row concept and he made no conclusions on the rate relationship between methods. Lewis and Strickland (1944) conc_Iuded the follo~ ing: "Fertilizers were twice as effecuve when sown m the drills as when broadcast. On an average, broadcast fertilizer increased the yields of grain and straw by 4.0 and 6.3 cwtjaere, respectively.…”
Section: G a Peterson D H Sander P H Grabouski And M L Hooker2mentioning
confidence: 99%
“…Moreover, for the basal as well as the boronated manurial treatments, the concentra- 48 tion of boron in the different parts of the plant was greater when the manure had obtained better contact with the germinating seedlings by being sown in the drills instead of being broadcast. This finding is of interest in view of the attention that has been paid recently to the placement of manures in relation to the seed (Lewis, 1941;Lewis & Strickland, 1944). If, as found in the experiments described above, the concentration of boron in the young plant is increased by sowing manures in the drill rather than broadcast, it is probable that the concentration of other nutrients in the young plant (e.g.…”
Section: Effect On Boron Uptake Of Broadcasting or Sowing Manures In mentioning
confidence: 72%